Modulation of Apoptosis by Bovine Gammaherpesvirus 4 Infection in Bovine Endometrial Cells and the Possible Role of LPS in This Process - Romeo, Florencia; Delgado, Santiago Germán; Yavorsky, Marisol; Martinez Cuesta, Lucía; Pereyra, Susana Beatriz; González Altamiranda, Erika; Louge Uriarte, Enrique Leopoldo; Pérez, Sandra; Verna, Andrea Elizabeth (MDPI, 2024)
The prevalent pathogens associated with bovine uterine infections are bacteria that appear to increase the host’s susceptibility to secondary infections with other bacteria or viruses, among which BoGHV4 is the most frequently found. In this work, the study of the pathways of apoptosis induction was carried out on an experimental model of primary culture of endometrial cells, in order to know the implication of BoGHV4 and the presence of bacterial LPS in the pathogenesis of the bovine reproductive tract. For this, different staining techniques and molecular analysis by RT-PCR were used. The results obtained allowed us to conclude that the level of cell death observed in the proposed primary culture is directly related to the time of viral infection and the presence of LPS in BoGHV4 infection. The apoptosis indices in cells infected with BoGHV4 and BoGHV4 + LPS revealed a maximum that correlated with the appearance of cytopathic effects and the maximum viral titers in the model studied. However, morphological, biochemical, and molecular changes were evident during both early and late stages of apoptosis. These findings provide information on the factors that may influence the pathogenesis of BoGHV4 and help to better understand the mechanisms involved in virus infection.